A efetividade das informações disponibilizadas no portal corporativo de uma instituição pública de ciência e tecnologia para o compartilhamento do conhecimento - Hartke, Andrea de Mesquita (2018)
The changes occur quickly and the technological advances are remarkable in the management. In this context, organizations need to be dynamic and special attention must be given to the institutional knowledge management. Knowledge management requires coordinated and collaborative action among the people involved in the process, allowing institutions to avoid recurring failures, improve practices and leverage their results. These factors create competitive advantage for the institution. Thus, this exploratory and descriptive research had as general objective to identify the effectiveness of the information available in the corporate portal of a public institution of science and technology for the sharing of knowledge. The results obtained, analyzed in a predominantly qualitative way, allow us to conclude that the intranet is being partially effective, since it is the main information search channel of the institution and has a high frequency of weekly accesses. However, 11 of the 15 analyzed sectors presented indexes above 50% of non-access to their available content and 50% of users consider that their contents are organized and structured in order to partially meet the need for knowledge of the institute. Also, the intranet is the main element for sharing knowledge, followed by an organizational environment that favors the exchange of ideas, freedom of communication and organizational culture. It is possible to infer that this technological tool contributes positively to the knowledge management, but it is necessary to improve and adapt the information with the maintenance and expansion of the environment favorable to the exchange of knowledge and stimulation of the culture of knowledge and learning to achieve better institutional results.